Value of expression of insulin-like growth factor-1 receptor in gastric adenocarcinomas and normal gastric tissues - Ömer Topalak; Funda Uğur Kantar; Çağnur Ulukuş; Ali Küpelioğlu (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Insulin-like growth factor-1 receptor (IGF-1R) plays critical roles in cell proliferation, differentiation, apoptosis, and transformation. Suppression of IGF-1R by means of antisense methods and specific antibodies causes cell apoptosis and growth inhibition of cancer cells. The present study aims to investigate whether there is a difference between normal and cancerous tissue with respect to IGF-1R expression and to assess the relationship between IGF-1R expression and tumor stage, degree of differentiation, and lymph node metastasis by examining IGF-1R expression in cancerous and normal tissues of gastric adenocarcinoma cases of different stages. Materials and Methods: By using immunohistochemical methods, IGF-1Rb (H-60) (1/100, Santa Cruz Biotechnology, SC-9038, Texas,USA) expression was investigated in paraffin-embedded blocks obtained from total/partial gastrectomy material pertaining to 47 gastric adenocarcinoma cases. IGF-1R expression was evaluated semi-quantitatively in terms of intensity and distribution in both normal and cancerous tissues. Results: Insulin-like growth factor-1 receptor expression mean score was 5.38 and 8.40 for cancerous and for normal gastric tissues, respectively. IGF-1R expression decreased significantly in cancerous tissues compared normal tissue (p:0.001). When all cases with and without lymph node metastasis were analyzed, IGF-1R expression was observed to decrease for cases with lymph node metastasis compared to those without lymph node metastasis (p:0.035). Conclusion: Insulin-like growth factor-1 receptor expression in gastric cancer tissue has proven to be considerably lower than IGF-1R expression in normal gastric mucosa. Metastatic progression reduces IGF-1R expression gradually in cancer tissue.